Numerical solution of integral equations system of the second kind by Block–Pulse functions - Maleknejad, K.; Shahrezaee, M.; Khatami, H. (Applied mathematics and computation, 2005)
This paper endeavors to formulate Block–Pulse functions to propose solutions for the Fredholm integral equations system. To begin with we describe the characteristic of Block–Pulse functions and will go on to indicate that through this method a system of Fredholm integral equations can be reduced to an algebraic equation. Numerical examples presented to illustrate the accuracy of the method.